Masculinidades e atos infracionais: a compreensão de jovens em conflito com a lei sobre as questões de gênero - Gomes, Ananda Evelyn Cardoso (Universidade Federal de São Carlos, 2020)
This research is of a qualitative nature and aimed to discuss and analyze the conceptions of young authors of infractions on masculinities, in the city of Sorocaba/SP, problematizing from their speeches and trajectories the association between gender and conflict with the law. Individual interviews were carried out with five young people, initially with questions related to conceptions about gender and masculinities. In a second step, questions were asked about the intersection between gender and race, ending with questions related to the offending acts. The interviews resulted in different statements, some contradictions in relation to the conceptions of masculinities and situations experienced by young people, but they also expressed desires and feelings in relation to expectations for the future, about economic limits, their social relations and situations of social exclusion.
Masculinities and infractions: the understanding of young people in conflict with the law about gender issues
Keywords: Jovens; Conflito com a lei; Gênero; Masculinidades; Youth; Conflict with the law; Gender; Masculinity; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO